Ghost cell odontogenic carcinoma of the left maxilla. Issue 4 (22nd April 2021) - Oliveira Santos, Pedro; Cabrera, Rafael; Vilares, Miguel; Borges, Alexandra
Abstract : We report the case of a 25-year-old man with a maxillary ghost cell odontogenic carcinoma (GCOC). The patient presented to the maxillofacial and head and neck surgery clinic with a growing lump in the left maxilla. Initial workup with CT revealed a cystic lesion in the left upper jaw with associated bone erosion and an enhancing soft-tissue component. Enucleation showed a GCOC associated with a calcifying odontogenic cyst. After the diagnosis was obtained, the patient underwent widening of the first surgical resection. GCOCs are rare odontogenic neoplasms with unspecific clinical and imaging presentation, whose definitive characterisation is based on pathology. Current treatment approaches mainly involve surgical excision, but the prognosis is highly unpredictable due to intertumoral heterogeneity. As tumour recurrences occur in 73% of cases, radical surgery with negative margins is highly recommended. Therefore, it is essential to recognise this entity to offer patients adequate management.